Production systems and soil fertility of Hass avocado in Oaxaca - Velasco-Velasco , Lidia; Trujillo-García, David; Díaz-Nuñez, José Luis; Solís-Martínez, Martín; Flores-Hernández, Luis Antonio; Cruz-Santiago, Michell Deyanira (Revista Mexicana de Ciencias Agrícolas, 2026)
Avocado production has experienced remarkable growth in recent decades, positioning itself as an important agricultural activity in Mexico. The increase in productivity is threatened by multiple factors that intervene in production, including adverse climatic conditions derived from climate change; therefore, proposing alternatives that may have a lower environmental impact is of great importance. The objective was to study production systems with respect to fertilization management, their effects on soil conditions, and their relationship with yield in Hass avocado production units in the state of Oaxaca. Twenty-eight production units were studied in the Sierra Sur region in Villa Sola de Vega and in the Valles Centrales region in Zaachila; they presented three types of production systems: agroecological (organic fertilization), conventional (synthetic fertilizers) and combined (alternation between both). Soil sampling was carried out for fertility analysis in accordance with NOM-021-RECNAT and yield was estimated. Analysis of variance indicated statistically significant differences in iron (Fe) content and yield only. The best results in terms of improving soil fertility were obtained under agroecological management, whereas the highest yields were recorded in units with combined management. There was a significant positive correlation of Ca with BD, pH, EC, N, Na, and Fe. Agroecological management significantly improved soil properties; however, during the production cycle analyzed, no increase in yield was obtained.
Keywords: agroecological management; climate change; inorganic fertilization; production systems